Surgical debridement with VERSAJET: an analysis of bacteria load of the wound bed pre‐ and post‐treatment and skin graft taken. A preliminary pilot study - Fraccalvieri, Marco (Int Wound J, 2011)
Surgical debridement, which is used for the removal of necrotic tissue from a wound, is becoming more and more important in the treatment of skin injuries. VERSAJET (VERSAJET™, Versajet Hydrosurgery System, Smith and Nephew, Hull, UK) is one of the techniques used for wound debridement. Medical literature does not present either analytical or comparative data correlating the bacterial load with the VERSAJET treatment. For this reason, we have decided to carry out a study to evaluate the level of bacterial contamination before and after the surgical debridement treatment with VERSAJET and, in connection with this, the correlation between the bacterial load and the successful healing of the skin graft. We took a total of 100 bacteriological swabs, 50 before and 50 from 27 selected patients after the treatment with VERSAJET, with which the wound bed was prepared to receive the skin graft or Integra graft in order to acquire data about the level of bacterial contamination. After analysing all those data we can assume that reducing the bacterial load is not the only variable which the successful healing of the skin graft depends on. In conclusion, there is still many data to analyse and study in order to better understand the qualitative and quantitative presence of bacteria and the success of this future surgical procedure. We remind that the performance of this study was not sponsored by any company.